PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DINAS KOPERASI DAN UKM KABUPATEN SAMPANG DENGAN KEMAMPUAN MANAJERIAL SEBAGAI VARIABEL MEDIASI - Zubaidi Zubaidi; Chamariyah Chamariyah (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The type of research is explanatory research using a quantitative approach, the research sample is 35 respondents (the sampling technique uses the saturated sample method), the data analysis uses GeSCA (Generalized Structured Component Analysis) analysis. The objectives of this study are: 1) To examine and analyze the effect of motivation on managerial ability in the Department of Cooperatives and SMEs in Sampang Regency. 2) To test and analyze the effect of managerial ability on the performance of the employees of the Cooperatives and SMEs Office of Sampang Regency. 3) To examine and analyze the effect of motivation on the performance of the employees of the Cooperatives and SMEs Office of Sampang Regency. 4).To examine and analyze the effect of motivation on the performance of the employees of the Cooperatives and SMEs Office of Sampang Regency which is mediated by managerial ability. The results showed that: 1) Motivation had a significant negative effect on managerial ability in the Department of Cooperatives and SMEs in Sampang Regency with a CR value of -0.38; 2) Managerial ability has a significant effect on employee performance at the Cooperatives and SMEs Office of Sampang Regency with a CR value of 2.33; 3) Motivation has a significant effect on employee performance at the Cooperatives and SMEs Service Office of Sampang Regency with a CR value of 4.87; 4) Motivation has a significant effect on employee performance which is mediated by managerial ability with a CR value of 11.40.